Pengaruh Word of Mouth dan Persepsi Harga terhadap Keputusan Pembelian pada Cilok Goang Uruy Tasikmalaya - Febri Herdiana; Budhi Wahyu Fitriadi; Ari Arisman (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2022)
This study aims to determine the effect of word of mouth and price perception on purchasing decisions at Cilok Goang Uruy. The method used in this study is causality through a survey approach. With a research sample of 100 consumers of Cilok Goang Uruy Golacir Tasikmalaya. The data used is primary data. The analytical tool used in this study is multiple regression using SPSS 26.0. The results showed that the word of mouth and price perception had a significant influence on purchasing decisions at Cilok Goang Uruy Golacir Tasikmalaya. Partially, Word of Mouth has a significant influence on purchasing decisions at Cilok Goang Uruy Golacir Tasikmalaya. Partially, price perception has a significant influence on purchasing decisions at Cilok Goang Uruy Golacir Tasikmalaya